AN IMPROVED SECURITY FRAMEWORK IN HEALTH CARE USING HYBRID COMPUTING - Devi, B. S. Kiruthika; Vijayakumar , V; Suseela, G; Kavin, B. Prabhu; Sivaramakrishnan, S.; Rodrigues, Joel J. P. C. (Malaysian Journal of Computer Science, 2022)
Cloud computing is a new category of service that gives each customer access to a large-scale computing network. Since most cloud computing platforms provide services to a large number of people who aren't considered to be trustworthy, various cyber attacks may potentially target them. As a result, a cloud computing system must provide a security monitoring mechanism to protect the Virtual Machine from attacks. In this case, there is a tradeoff between the security level of the security system and its performance. If we need strong security, we'll need more laws or patterns, which means we'll need a lot more computational resources in proportion to the strength of security. As a result of the declining number of resources allocated to customers, we will add a new protection scheme in cloud environments to the VM in this report. Hence, the proposed system Proposed Elliptic curve – Diffie Hellman EC(DH)2 Algorithm is designed and deployed to improve the security in healthcare domain using hybrid computing. The most popular and recent technologies such as cloud computing and fog computing are integrated to explore data movement and stable medical data health-care information. Based on the experimental results, it is inferred that the proposed system offers high security and less operating time while handling the data making its deployment in the healthcare domain.